Factors influencing knowledge sharing between scientific specialists in knowledge networks and communities of practice: A systematic literature review - Mina Mahami-Oskouei; Leila Nemati-Anaraki; Sirous Panahi; Shadi Asadzandi (Wolters Kluwer Medknow Publications, 2024)
Knowledge sharing is a competitive advantage and necessity for the success of any organization. Meanwhile, knowledge networks have been introduced as a way to enhance knowledge sharing between individuals and as an effective tool to facilitate knowledge exchange in clinical, educational, and commercial fields. The purpose of this paper is to identify the factors that can affect the level of knowledge sharing and exchange between academic and scientific specialists in knowledge networks and Communities of Practice (COP). A systematic literature review was conducted using the PRISMA guidelines. Four databases were searched, including Scopus, Web of Science, PubMed, and ProQuest. Google Scholar search was conducted to complete the search and ensure the tracking of the gray literature. Also, relevant sources, references, and reference lists of the related articles were reviewed. The studies were searched from April until August 2022 and finally the content analysis of the findings was done. Two reviewers independently assessed the quality of included studies. Data were extracted using the Joanna Briggs Institute (JBI) checklist tool. Of the 1439 records, 13 studies met the inclusion criteria. This study identified three main categories of factors affecting knowledge sharing in knowledge networks and COPs as individual factors, organizational, and structural. The results showed that knowledge networks provide opportunities to overcome professional barriers and complex systemic challenges and lead to knowledge sharing and exchange among scientific specialists. This article has important implications for managers, health policymakers, and academics who wish to expand knowledge sharing of scientific specialists through knowledge networks and CoPs in knowledge-based organizations.